Perinatal outcome in relation to maternal glycaemic control in gestational diabetes mellitus - K., Kanmani; Subramanian, Sudha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Early diagnosis and treatment of gestational diabetes with adequate antenatal care are essential to reduce the adverse neonatal outcomes. Methods: All selected women were subjected to a detailed history taking comprising of age, parity, prepregnant body weight, medication history, family history, medical history, detailed obstetric history. Then they were subjected to clinical examination and routine laboratory investigations. Antenatal women were diagnosed with GDM, when 75gm GCT ≥140mg/dl based on DIPSI criteria. Fasting and postprandial blood sugars (2hours) were done and if FBS and PPBS were normal, the patient was labelled as GDM on meal plan. If fasting > 96 mg/dl and 2-hr postprandial blood sugar >121 mg/dl, Inj.insulin was started. Patients were managed according to the FBS and PPBS values throughout antenatal period and the perinatal outcomes were studied. Results: Among 150 patients, multiparous women constitute 65.3% and primi 34.7%. 60% of the patients were in age group of 26 to 30 years.59.3% of patients were in BMI of range 25 to 30.Family history of diabetes was present in 24.7% of the patients. Previous history of GDM was present in 27.3% of cases.98% of GDM were detected in 2nd trimester. The percentage of cases presented with macrosomia was 8.7%, RDS 3.3%, hypoglycaemia 6%, hyperbilirubinemia 3.3%, IUD 0.7%, perinatal injury 1.3%, NICU admission requiring ≥3 days of admission was 12%. Conclusions: There is association of elevated FBS and PPBS values with occurrence of adverse perinatal outcome.